Association of the abdominal aortic calcification with all-cause and cardiovascular disease-specific mortality: Prospective cohort study - Chang Sheng; Zhou Cai; Pu Yang (PLoS ONE, 2025)
Background Abdominal aortic calcification (AAC) is a prevalent form of vascular calcification associated with adverse cardiovascular outcomes. While previous studies on AAC and cardiovascular risk exist, many have limitations such as small sample sizes and limited clinical significance outcomes. This study aims to prospectively investigate the association between AAC and all-cause and cardiovascular disease (CVD)-specific mortality rates in a nationally representative sample of adults in the United States, using data from the National Health and Nutrition Examination Survey (NHANES). Methods The study, conducted on NHANES participants aged 40 years or older during the 2013–2014 cycle, assessed AAC using the Kauppila scoring system. Demographic characteristics, mortality data, and comorbid factors such as age, gender, diabetes, and hypertension were considered. Statistical analyses, including weighted percentages, Kaplan-Meier survival curves, and multivariable Cox proportional hazards regression models, were employed to evaluate the associations between AAC and mortality risks. Results After analyzing a final sample of 2717 participants, the study found a significant association between severe AAC (SAAC) and higher all-cause mortality risk (HR 1.70, 95% CI 1.17–2.48). The dose-response relationship indicated an increased risk with higher AAC scores. However, no independent association was observed between AAC and cardiovascular mortality. Stratified analysis revealed variations in the AAC-all-cause mortality association based on gender and hypertension. Conclusion This population-based study provides valuable insights into the prospective association between AAC and all-cause mortality, emphasizing the potential role of AAC assessment in identifying individuals at higher risk.